Cumulative dietary risk assessment overarching different regulatory silos using a margin of exposure approach: A case study with three chemical silos. (August 2020) - Sprong, Corinne; Crépet, Amélie; Metruccio, Francesca; Blaznik, Urska; Anagnostopoulos, Chris; Christodoulou, Despo Louca; Jensen, Bodil Hamborg; Kennedy, Marc; González, Neus; Rehurkova, Irena; Ruprich, Jiří; te Biesebeek, Jan Dirk; et al.
Abstract: Risk assessment of chemicals occurring in our diet is commonly performed for single chemicals without considering exposure to other chemicals. We performed a case study on risk assessment of combined dietary exposure to chemicals from different regulatory silos, i.e. pesticides (PPRs), persistent organic pollutants (POPs) and food additives (FAs). Chemicals were grouped into the cumulative assessment group (CAG) liver steatosis using a component-based approach. Based on literature, the CAG included 144 PPRs, 49 POPS and 7 FAs for which concentration data were available. For each silo, chronic combined dietary exposure was assessed for adults and children of nine European countries following the most commonly used exposure methodologies in Europe and by using a relative potency factor approach. For risk characterization, a Margin of Exposure (MOE) was calculated. To overarch the risk across silos, a normalised combined margin of exposure (nMOET) approach was proposed. This case study demonstrated that risk assessment of combined exposure to chemicals can be performed within regulatory silos. It also highlighted important differences in the conservatism of exposure scenarios, the derivation of point of departures and the subsequent acceptable MOEs between the silos. To overarch the risk despite these differences, a nMOET approach can be used.